2020
DOI: 10.1136/bmjopen-2019-035265
|View full text |Cite
|
Sign up to set email alerts
|

Translating the Symptom Screening in Pediatrics Tool (SSPedi) into French and among French-speaking children receiving cancer treatments, evaluating understandability and cultural relevance in a multiple-phase descriptive study

Abstract: ObjectivesSymptom Screening in Pediatrics Tool (SSPedi) is a validated approach to measuring bothersome symptoms for English-speaking and Spanish-speaking children with cancer and paediatric haematopoietic stem cell transplantation (HSCT) recipients. Objectives were to translate SSPedi into French, and among French-speaking children receiving cancer treatments, to evaluate understandability and cultural relevance.MethodsWe conducted a multiphase, descriptive study to translate SSPedi into French. Forward trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…3 It has been translated into Spanish and French. 11 The most commonly reported bothersome symptoms are shown in Figure 2. A self-report version for children 4 to 7 years of age (mini-SSPedi 12 ) and a proxy-report version for children 2 to 18 years of age 13 have also been developed.…”
Section: Symptom Screening In Routine Carementioning
confidence: 99%
“…3 It has been translated into Spanish and French. 11 The most commonly reported bothersome symptoms are shown in Figure 2. A self-report version for children 4 to 7 years of age (mini-SSPedi 12 ) and a proxy-report version for children 2 to 18 years of age 13 have also been developed.…”
Section: Symptom Screening In Routine Carementioning
confidence: 99%
“…We translated SSPedi into French and found that the translated version was understandable and culturally appropriate in Canada and France. 8 We also focused on translation to Spanish. 9 During this translation process, we identified that at least two versions of Spanish would be required, namely, one appropriate for North America and one appropriate for Argentina.…”
Section: Introductionmentioning
confidence: 99%